2007
DOI: 10.1038/sj.bjc.6603934
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in five genes important in telomere biology and risk for breast cancer

Abstract: Telomeres, consisting of TTAGGG nucleotide repeats and a protein complex at chromosome ends, are critical for maintaining chromosomal stability. Genomic instability, following telomere crisis, may contribute to breast cancer pathogenesis. Many genes critical in telomere biology have limited nucleotide diversity, thus, single nucleotide polymorphisms (SNPs) in this pathway could contribute to breast cancer risk. In a population-based study of 1995 breast cancer cases and 2296 controls from Poland, 24 SNPs repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 28 publications
(39 reference statements)
5
76
2
2
Order By: Relevance
“…This gene is widely expressed in different tissues; however, its function is largely unknown. Several studies have revealed that the common polymorphisms of CLPTM1L are associated with multiple types of cancers, including lung cancer (Savage et al, 2007;Wang et al, 2008;Gago-Dominguez et al, 2011;Nan et al, 2011). In the most recently published study, Ke et al (2013) confirmed the association between the T allele of rs401681 and reduced risk of lung cancer in a Chinese population.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This gene is widely expressed in different tissues; however, its function is largely unknown. Several studies have revealed that the common polymorphisms of CLPTM1L are associated with multiple types of cancers, including lung cancer (Savage et al, 2007;Wang et al, 2008;Gago-Dominguez et al, 2011;Nan et al, 2011). In the most recently published study, Ke et al (2013) confirmed the association between the T allele of rs401681 and reduced risk of lung cancer in a Chinese population.…”
Section: Discussionmentioning
confidence: 76%
“…CLPTM1L gene encodes a predicted transmembrane protein, but its function is largely unknown. Several studies have reported that the common polymorphisms of CLPTM1L are associated with the risk for development of various cancers, such as bladder cancer, skin cancer, lung cancer, breast cancer (Savage et al 2007;Wang et al, 2008;Gago-Dominguez et al, 2011;Nan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of both Asian and European individuals, the TERT rs2736098 polymorphism was identified as a likely contributor to increased risk of developing bladder cancer in individuals of Asian ancestry (Gago-Dominguez et al, 2011). A study based on the European population found that TERT rs2736098 shows a borderline statistically significant association with reduced risk of breast cancer in analysis of all cases and controls; however, the association appeared to be stronger for individuals with a family history of breast cancer (Savage et al, 2007).…”
Section: Tert Rs2736098 Polymorphism and Cancer Risk: Results Of A Mementioning
confidence: 99%
“…Although several studies in recent years have focused on the association between the TERT rs2736098 polymorphism and cancer susceptibility, the results are inconclusive (Savage et al, 2007;Jin et al, 2009;Liu et al, 2010;Chen et al, 2011;Gago-Dominguez et al, 2011) . Therefore, this meta-analysis was performed to evaluate whether the TERT rs2736098 polymorphism is truly associated with cancer risk.…”
Section: Tert Rs2736098 Polymorphism and Cancer Risk: Results Of A Mementioning
confidence: 99%
See 1 more Smart Citation